2020
DOI: 10.21203/rs.3.rs-118051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of Household Catastrophic and Impoverishing Health Expenditures among Patients with Breast Cancer in Iran

Abstract: Background: Breast cancer disease is the most common cancer among Iranian women. Management of this disease requires expensive services and care, imposing a significant financial burden on the households. This study calculated out-of-pocket (OOP), catastrophic health expenditure (CHE), and impoverishing health spending attributed to breast cancer in Iran.Methods: In this cross-sectional household study, clinical and financial information on breast cancer and also household information (expenditures and income)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…In term of sociodemographic factor, higher socioeconomic group spend significantly higher out of pocket. Higher household income showed higher OOP which is similar to other study 9 . Several studies found lower income group associated with lower OOP and a factor contributing to financial toxicity 10 and higher OOP burden 11 while the proportion of households facing catastrophic OOP health payments were more prevalent in poor income states and aggravate the prevalence and intensity of poverty by the need to pay for health care services 12 .…”
Section: Discussionsupporting
confidence: 90%
“…In term of sociodemographic factor, higher socioeconomic group spend significantly higher out of pocket. Higher household income showed higher OOP which is similar to other study 9 . Several studies found lower income group associated with lower OOP and a factor contributing to financial toxicity 10 and higher OOP burden 11 while the proportion of households facing catastrophic OOP health payments were more prevalent in poor income states and aggravate the prevalence and intensity of poverty by the need to pay for health care services 12 .…”
Section: Discussionsupporting
confidence: 90%